2001
DOI: 10.1007/s004420000531
|View full text |Cite
|
Sign up to set email alerts
|

How do visitation patterns vary among pollinators in relation to floral display and floral design in a generalist pollination system?

Abstract: Diverse pollinator assemblages may impose complex selection and thus limit specialisation to particular pollinators. Previous work has concentrated on how visitation rates of different pollinators vary in space and time and how pollinators may vary in efficiency. In this study I quantify variation in visitation rates and foraging behaviour of different insect types (1) in space and time and (2) in relation to variation in floral design (flower size and form) and floral display (number of open flowers) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
161
2
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(182 citation statements)
references
References 58 publications
(60 reference statements)
6
161
2
13
Order By: Relevance
“…Dioecious plants tend to have small flowers pollinated by unspecialized, opportunistic insects and fleshy fruit dispersed by animals (Bawa, 1980; Ibarra‐Manriquez & Oyama, 1992). Thompson (2001) reported that the number of visits by opportunistic pollinators was positively related to the number of open flowers in a patch of a shrub species, but such a positive relationship between floral display and visitation rate was not true for specialist pollinators. The precocity of dioecious plants may facilitate their reproduction by attracting generalist pollinators via increased reproductive plant density.…”
Section: Discussionmentioning
confidence: 99%
“…Dioecious plants tend to have small flowers pollinated by unspecialized, opportunistic insects and fleshy fruit dispersed by animals (Bawa, 1980; Ibarra‐Manriquez & Oyama, 1992). Thompson (2001) reported that the number of visits by opportunistic pollinators was positively related to the number of open flowers in a patch of a shrub species, but such a positive relationship between floral display and visitation rate was not true for specialist pollinators. The precocity of dioecious plants may facilitate their reproduction by attracting generalist pollinators via increased reproductive plant density.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a greater number of flowers might mean a reduction of, or no effect on, the visitation rate of each individual flower (Klinkhamer & Jong 1990;Mitchell et al 2004;Grindeland et al 2005). Likewise, a high density of flowering individuals in an area might lead to enhanced visitation for each due to facilitation (Kunin 1997;Thompson 2001;Moeller 2004;Makino & Sakai 2007;Brys & Jacquemyn 2010;Hegland 2014). Nonetheless, high densities of individuals that overlap in flowering, both in time and space, might cause competition for pollinators, leading to decreased visitation rates per individual (Mustajärvi et al 2001;Sargent & Ackerly 2008;Hegland 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular-mycorrhizal fungi (AMF) form associations with the roots of most vascular plant species, consuming photosynthate and often providing enhanced nutrition or other benefits (Allen et al 1991). Because of the intimacy of the plant-AMF interaction, mycorrhizal suppression can have widespread direct and indirect effects on plant communities, including shifts in species diversity , altered competitive outcomes (Smith et al 1999), and increased growth of non-mycorrhizal or weakly mycorrhizal species (van der Heijden et al 1998). As mycorrhizae can affect both floral trait expression of individuals (Gange andSmith 2005, Wolfe et al 2005) and plant community composition , there is reason to expect mycorrhizae to influence plant-pollinator interactions.…”
Section: Introductionmentioning
confidence: 99%